2021
DOI: 10.1002/ange.202007693
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Photoresponsive Molecular Amphiphiles in Aqueous Media

Abstract: Amphiphilic molecules, comprising hydrophobic and hydrophilic moieties and the intrinsic propensity to self‐assemble in aqueous environment, sustain a fascinating spectrum of structures and functions ranging from biological membranes to ordinary soap. Facing the challenge to design responsive, adaptive, and out‐of‐equilibrium systems in water, the incorporation of photoresponsive motifs in amphiphilic molecular structures offers ample opportunity to design supramolecular systems that enables functional respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 279 publications
(411 reference statements)
0
14
0
Order By: Relevance
“…3,[8][9][10][11] The mechanism of solute-solute interactions in these assemblies is well-established, 1,2,4 whereas the solute-solvent interplay attracted the interest of supramolecular chemists more recently. [12][13][14] Water is a unique medium for self-assembly in Nature, and many exquisite assemblies, [15][16][17][18][19][20][21][22][23][24] low-molecular-weight gels, [25][26][27][28][29] and supramolecular polymers [30][31][32][33][34][35][36] have been developed in aqueous media focusing on various applications, such as biomolecular materials 37,38 and soft actuators. [39][40][41] However, detailed insight into supramolecular polymerization in water is far from being as well understood as it is in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10][11] The mechanism of solute-solute interactions in these assemblies is well-established, 1,2,4 whereas the solute-solvent interplay attracted the interest of supramolecular chemists more recently. [12][13][14] Water is a unique medium for self-assembly in Nature, and many exquisite assemblies, [15][16][17][18][19][20][21][22][23][24] low-molecular-weight gels, [25][26][27][28][29] and supramolecular polymers [30][31][32][33][34][35][36] have been developed in aqueous media focusing on various applications, such as biomolecular materials 37,38 and soft actuators. [39][40][41] However, detailed insight into supramolecular polymerization in water is far from being as well understood as it is in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Light as a contactless stimulus offers multiple advantages such as tunable optical wavelength and intensities as well as high temporal and spatial control. Several classes of photoresponsive amphiphilic molecules are distinguished: intrinsic light-switches, photoresponsive molecular amphiphiles (a photoresponsive unit is chemically included into a classical surfactant “head-tail” structure), and photoresponsive supramolecular amphiphiles (a photoresponsive component is introduced via noncovalent interactions) [ 1 ]. The self-organized ensembles of photoresponsive amphiphiles manipulated by light fundamentally enable new pathways towards aqueous bio-compatible materials, that can change certain properties in a predictable manner or can provide best performance when operation circumstances change [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Azobenzene-containing surfactants (azo-surfactants) are usually used as an additive in multicomponent formulations to elicit a photoresponse from systems as a whole. , The use of azo-surfactants as the sole surfactant in micellar self-assemblies is less common, and studies on their structure–behavior relationships in this area are less comprehensive, although some discussion of the electronic properties of such materials and how this relates to their use in supramolecular (assembled) systems has been recently made in the literature. , Rational design of new azo-surfactants requires an understanding of the role that incorporated structural motifs will play in the properties of both trans and cis isomers. Previous studies utilizing neutral azo-surfactants have shown that even small changes in the size and polarity of the head group or linker (Figure ) can facilitate large changes in the solubility and aggregate morphology of azo-surfactants. ,, …”
Section: Introductionmentioning
confidence: 99%
“…23,27 The use of azo-surfactants as the sole surfactant in micellar self- assemblies is less common, and studies on their structure− behavior relationships in this area are less comprehensive, although some discussion of the electronic properties of such materials and how this relates to their use in supramolecular (assembled) systems has been recently made in the literature. 28,29 Rational design of new azo-surfactants requires an understanding of the role that incorporated structural motifs will play in the properties of both trans and cis isomers.…”
Section: ■ Introductionmentioning
confidence: 99%